Exploring Pre-Service English Teachers’ Knowledge toward GBA Approach in Indonesian EFL Curriculum - Ramadhan, Rizki; Ficayuma, Lina Aris; Anang Darmawan, Achmad (ETERNAL (English Teaching Journal), 2024)
The aim of research was to figure out pre-service English teachers’ capability, in order to comprehend and to implement the Genre-Based Approach (henceforth, GBA) in EFL classrooms. This study used a qualitative case study approach to investigate the understanding of pre-service English teachers towards the GBA in the Indonesian newest curriculum, called Kurikulum Merdeka (Independent Curriculum). The research was conducted at Al Hikmah Teacher Institute. Non probability with purposive sampling type is a technique was used to select the participants. Furthermore, for further understanding of the data, some selected participants were interviewed by the researcher. In this study, questionnaires, structured interviews, and document collection were applied as instruments. The interactive model of data analysis proposed by Miles and Huberman was adopted in analyse the data. In short, the study revealed three findings, there are; 1) most of the pre-service English teachers (71.5%) of the participants did have not sufficient knowledge; 2) the rest of the participants (28.5%) had sufficient knowledge of the content knowledge (henceforth, CK); and 3) the implementation of the GBA in English Language Teaching (henceforth, ELT).